Analysis of security possibilities of platforms for 3D graphics - Horálek Josef; Svoboda Tomáš (My University, 2016)
This paper introduces the results of an analysis of security threats based on 3D graphics interface abuse mainly in Windows operating systems. Basic security threats, which can greatly influence the functionality and security of an operating system, are introduced in this paper. Due to the specific nature of the operating systems architecture, the most vulnerable part are the third party drivers, which have access to the core mode. Different approaches of protecting drivers are described together with disadvantages of these solutions. Practical methods of attacks are discussed in detail and when relevant, program alterations are suggested to program designers. The goal of these suggestion is to minimize or to completely eliminate mentioned security threats, making 3D graphics interface more secure.
Analýza možností zabezpečení platformy pro 3D grafiku
Keywords: security, 3d graphics, buffer overflow, timing attack, object slicing; bezpečnost, 3d grafika, buffer overflow, načasování útoku, škálovatelnost